Secrecy Throughput of MANETs Under Passive and Active Attacks - Yingbin Liang; Poor, H. V.; Lei Ying (IEEE transactions on information theory, 2011)
The secrecy throughput of mobile ad hoc networks (MANETs) with malicious nodes is investigated. The MANET consists of n legitimate mobile nodes and m malicious nodes. Transmissions between legitimate nodes are subject to a delay constraint D . A model under passive attack is first studied, in which the malicious nodes are assumed to be eavesdroppers that only listen to transmission without actively injecting signals. An information-theoretic approach for security is applied to achieve secure communication among legitimate nodes in MANETs with transmissions being kept perfectly secure from eavesdroppers. A critical threshold on the number of malicious nodes ( m ) is identified such that when m = o (√{ nD }), i.e., lim n→∞ m /√{ nD } = 0, the optimal secrecy throughput equals that of MANETs without malicious nodes, i.e., the impact of the presence of malicious nodes on the network throughput is negligible; and when m = Ω(√{ nD }poly( n )), i.e., lim n→∞ m /(√{ nD }poly( n )) ≥ c for a positive constant c, the optimal secrecy throughput is limited by the number of malicious nodes. A model under active attack is further studied, in which the malicious nodes actively attack the network by transmitting modified packets to the destination nodes. It is shown that to guarantee the same throughput as the model under passive attack, the model under active attack needs to satisfy more stringent condition on the number of malicious nodes.